Peran Kompensasi Memediasi Pengaruh Kepemimpinan Partisipatif Dan Pengembangan Karir Terhadap Work Engagement Karyawan Milenial - Sukmana, Oktiana Triperani; Martini, Ida Ayu Oka (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Study objective to to investigate the mediation effect of compensation on the relationship between participative leadership and work engagement, as well as the impact of career development, compensation, and participative leadership, career development, and work engagement. The research was conducted at BPJS Ketenagakerjaan offices in the Bali, Nusa Tenggara, and Papua regions, targeting millennial employees, with a sample size of 73 employees from each office, derived through proportional sampling. The analysis was conducted using structural equation models - Partial Least Squares (SEM-PLS), and data collection was conducted through questionnaires. The findings indicate that both participative leadership and career development positively and significantly influence compensation and work engagement among millennial employees at BPJS Ketenagakerjaan. Specifically, participative leadership directly impacts both compensation and work engagement, while career development affects these variables through the mediation of compensation. The study underscores the importance of enhancing participative leadership and career development to improve employee engagement and compensation within public service organizations like BPJS Ketenagakerjaan